2013
DOI: 10.1007/978-3-642-39998-5_6
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Sub-regular Complexity

Abstract: Abstract. We present a measure of cognitive complexity for subclasses of the regular languages that is based on model-theoretic complexity rather than on description length of particular classes of grammars or automata. Unlike description length approaches, this complexity measure is independent of the implementation details of the cognitive mechanism. Hence, it provides a basis for making inferences about cognitive mechanisms that are valid regardless of how those mechanisms are actually realized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 17 publications
1
89
0
Order By: Relevance
“…This approach has its roots in finite model theory (Enderton, 2001;Hedman, 2004;Courcelle & Engelfriet, 2012). (See Potts & Pullum (2002) and Rogers et al (2013) for model-theoretic approaches to phonology.) A relational structure contains a set of domain elements and a fixed number of relations over this set.…”
Section: Representing Candidatesmentioning
confidence: 99%
“…This approach has its roots in finite model theory (Enderton, 2001;Hedman, 2004;Courcelle & Engelfriet, 2012). (See Potts & Pullum (2002) and Rogers et al (2013) for model-theoretic approaches to phonology.) A relational structure contains a set of domain elements and a fixed number of relations over this set.…”
Section: Representing Candidatesmentioning
confidence: 99%
“…For example, *NC is a Strictly 2-Local constraint. See Rogers & Pullum (2011) and Rogers et al (2010Rogers et al ( , 2013 for details of these and other subregular languages. A formal definition of ISL functions similar to the informal one above is provided in Chandlee et al (2014), where mathematical relationships to the Strictly Local languages are explained and studied in more detail than we can provide here.…”
Section: Phonological Mapsmentioning
confidence: 99%
“…However, there is a well-studied hierarchy of sub-regular languages (McNaughton & Papert, 1971;Rogers & Pullum, 2011;Rogers et al, 2013), shown in Figure 3, that better capture the kinds of phonotactic patterns we observe in natural language (Heinz, 2009(Heinz, , 2010. At the very bottom of the sub-regular hierarchy lies the Strictly Local (SL) class of languages, which can be defined with grammars of permissible substrings of a certain length k. Consider the language in (5), which represents the allowable surface forms in a language with word-final obstruent devoicing.…”
Section: Strictly Local Functionsmentioning
confidence: 99%
“…On the other hand, the 'multiples of three a's' pattern in 3 is provably not Strictly Local for any value of k (see Rogers & Pullum (2011) and Rogers et al (2013) for details). In the next section, we extend this conception of locality to mappings.…”
Section: Strictly Local Functionsmentioning
confidence: 99%